Mechanical Behavior and Microstructural Characteristics of Ultradeep Tight Carbonate Rocks With Different Burial Depths - Zhang, Ran; Sun, Jianmeng; Cheng, Zhigang; Xin, Bixiao; Chen, Hao (Frontiers in Earth Science, 2022)
The rapid growth in energy demand has placed more attention on the exploration and development of oil and gas in ultradeep reservoirs. However, deep buried rocks in the special “three high” geological environment exhibit significantly different mechanical response characteristics and microstructural features compared with shallow rocks, which requires more targeted experiments and theoretical research. In this work, tight carbonate rocks obtained from five different burial depths ranging from 6077 to 6738 m are used to carry out quasi in situ triaxial compression tests under dry and saturated states. Combined with digital rock modeling based on computed tomography scans, the macromechanical responses and microstructural charactersites of the target samples with the variation of depth are analyzed. The results indicate that the long-term strength of deep rocks is much closer to the peak strength than that of shallow rocks, which can reach 94%–99% of the peak strength. The deeper-buried samples exhibit more pronounced plasticity under the same high confining pressure, and their elastic modulus is more likely to be weakened by pore water. Meanwhile, the ratios of residual strength to peak strength increase as the burial depth increases. Interestingly, the samples with weaker structures are more prone to alternate strain hardening and strain softening during the postpeak stage. On the other hand, the distribution of microstructural parameters for different depths is presented to help interpret the mechanical behaviors, and the difference in the dynamic and static elastic modulus of saturation is significantly connected with the mean pore–throat ratios. These results could provide a reference for research on deep rock mechanics.